Análise dos riscos ergonômicos para distúrbios osteomusculares nas atividades mono e multifuncionais de uma empresa de calçados - Leite , Wilza Karla dos Santos (2016)
Introduction: The incidence of Work-Related Musculoskeletal Disorders (WMSDs) has increased in various industrial sectors, including the footwear one, relating mainly to the exposition of ergonomic risk. The introduction of systems based on multifunctionality and job rotation has become an alternative to reduce WMSDs. Objective: To analyze the ergonomic risks factors related to musculoskeletal disorders in mono and multifunctional activities in a footwear company. Methodology: Research was conducted with 57 monofunctinoal and 57 multifunctional workers from a footwear company in Northeast Brazil. The Corlett and Manenica Diagram was used to assess pain and the Occupational Repetitive Actions (OCRA) method to categorize the level of ergonomic risk for WMSDs. Ordinal logistic regression models built were related to pain and individuals and work variables; multinomial logistic regression models were related to the levels of risk to variability in tasks executed by worker. Results: (1) Assessment of muscular-joint pain. It was identified that for the monofunctinal, the ocurrence of muscular-joint pain may be connected with length of service. For multifunctional ones, outcomes suggest that beyond length of service, the history of work-related diseases. However, it was ascertained that for length of service, the monofunctional demonstrated to be more vulnerable to pain in periods of exposure to the risk time less than the multifunctional worker; (2) Assessment of the risk level. From the activities performed by the monofunctinals, 14% present acceptable risk; 12.3% very low risk; and 73.7% have potential risk for WMSD (10.5%, mild; 36.8%, medium; and 26.4% high). Regarding the set of activities performed by multifunctionals, 10.5% are within acceptable limit; 8.8% have a very low risk; 80.7% presented a potential risk for WMSDs (10.5%, mild; 54.4% medium; and 15.8%, high). (3) Mathematical modeling according to the type of work. It was determined that for multifunctionals the representative variables covered cycle time (OR=0.92; p=0,0075) and number of activities performed by left upper limb in this cycle (OR=1.21; p=0,0044). For the multifunctional ones, the variable with significant effect was the weighted mean from OCRA index related to left upper limb (OR=1,22*102; p=0,0076). Furthermore, it was verified the significance regarding the range of motion utilized, the use gloves, and requirement of precision during task execution, suggesting that such factors may be associated to exposition of the multifunctional to WMSDs (p<0,05). (4) 10 Mathematical modeling according to the level of multifunctionality. The results were relevant to workers from first level of multifunctional training (OR=6,76*10-2; p=0,0431). Conclusions: It is concluded that (1) workers showed more susceptibility to muscular-joint pain when they perform just one function; (2) the activities carried out by both the workers have a representative risk for WMSDs, with a medium to high tendency risk for monofunctional ones and medium for the multifunctional ones; (3) for the multifunctional ones, there are evidences that more elevated risk are associated with the cycle of activity; (4) for the multifunctional ones, there are evidences that higher level are related with the excessive or inadequate requirement of left upper limb by combination of activities; (5) Specifically for the multifunctional ones, kinesiological aspects and the characteristics of activities can be connected to development of WMSDs; (6) the multifunctional ones, in a early stage of training, are exposed to lower WMSDs risks when compared to the ones who work more time in a same range of functions; and (7) multifunctional ones who perform a combination up to 30% of the total intracellular activities, appear to be less exposed to WMSD risk than the ones who execute a combination of large activities. Keywords: Footwear industry; kind of work; Ergonomics; WMSDs; mathematical modeling.